THE INFLUENCE OF METHOD OF SCREENING TUBERCULOSIS INFECTION WITH CHILDREN AND TEENAGERS ON THE FORMATION OF RISK GROUPS AND DISEASE DIAGNOSTICS - Ie. S. Ovsiankina; M. F. Gubkina; Panova; L. V. Panova (Педиатрическая фармакология)
.